PENGARUH KEPUTUSAN INVESTASI, STRUKTUR MODAL, DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN DENGAN PROFITABILITAS SEBAGAI VARIABEL INTERVENING (Studi Empiris Pada Perusahaan Infrastruktur di Bursa Efek Indonesia Tahun 2021-2023) - Andini Wisnu Trie Oktaviani Al-Fanani; Triyono (JURNAL ILMIAH EDUNOMIKA, 2026)
The aim of this study examined the influence of investment decisions, capital structure, and company size on firm value, with profitability as an intervening variable. This study used quantitative research methods with statistical analysis to test the hypotheses. The study population was all infrastructure companies listed on the Bursa Efek Indonesia (BEI) in 2021-2023. The sample was 37 infrastructure companies selected using a purposive sampling technique. Data were obtained through documentation and literature. Data analysis techniques used multiple regression analysis and path analysis. The results show that investment decisions, capital structure, and profitability partially have a positive and significant effect on firm value. Meanwhile, company size has a negative and significant effect on firm value. Profitability was an intervening variable that influences the relationship between investment decisions and firm value. Profitability was an intervening variable that influences the relationship between capital structure and firm value. Profitability was not an intervening variable that influences the relationship between firm size and firm value.